Self Efficacy and Self Awareness in Working Student Academic Stress: Efikasi Diri dan Kesadaran Diri dalam Mengatasi Stres Akademik pada Mahasiswa yang Bekerja - Ratrie Ayu Aprillia; Ghozali Rusyid Affandi (Academia Open, 2025)
ABSTRACTGeneral Background: Academic stress is a common psychological condition experienced by university students, particularly those who balance academic responsibilities with employment demands. Specific Background: Working students often encounter multiple academic and occupational pressures that may lead to psychological, emotional, and behavioral challenges affecting their academic performance. Knowledge Gap: Previous studies have examined determinants of academic stress, yet limited empirical evidence simultaneously investigates the roles of self efficacy and self awareness among working university students in a specific institutional context. Aims: This study aimed to determine the role of self efficacy and self awareness in academic stress among working students at Muhammadiyah University of Sidoarjo. Results: Using a quantitative approach with multiple linear regression on 263 respondents selected through purposive sampling, findings demonstrated that self efficacy and self awareness were significantly associated with academic stress (F = 80.42, p < .001), with both variables contributing 38.1% of the variance. Pearson correlation analysis revealed significant negative relationships between self awareness and academic stress (r = -0.545, p < .001) and between self efficacy and academic stress (r = -0.609, p < .001). Individual testing also confirmed significant negative associations of both variables with academic stress. Novelty: This study integrates self efficacy and self awareness as simultaneous predictors of academic stress specifically among working students in one institutional population. Implications: The findings provide empirical support for psychological development programs aimed at strengthening internal personal competencies to help working students manage academic stress and maintain academic engagement. Highlights: Combined Personal Competency Variables Explain 38.1% Variance of Stress Levels. Higher Confidence in Task Capability Corresponds With Lower Psychological Pressure. Increased Personal Recognition and Reflection Aligns With Reduced Educational Strain. Keywords: Academic Stress, Self Efficacy, Self Awareness, Working Students, Psychological Factors